Symbols, Diction, and the Meaning of Love in Three Poems from Asmaraloka by Usman Arrumy: A Hermeneutic Study: Simbol, Diksi, dan Makna Cinta dalam Tiga Puisi Asmaraloka Karya Usman Arrumy: Kajian Hermeneutika - Widia Astuti; Ach Ikhwanul Faris; Muhammad Subur; Atiqotul Fitriyah (The Future of Education Journal, 2026)
This study aims to describe and interpret the meaning of love in the poems "Namamu," "Kesaksian," and "Cita-Cita Rindu" from the poetry anthology Asmaraloka by Usman Arrumy using Paul Ricoeur’s hermeneutic approach. This research employed a qualitative descriptive method with a hermeneutic framework. Data were collected through reading and note-taking techniques, focusing on symbols, diction, and imagery that represent the concept of love in the selected poems. Data analysis was conducted through the stages of reading, understanding, explaining, and interpreting texts according to Ricoeur’s hermeneutic theory. The findings reveal that love is represented through three interconnected constructions of meaning: existential longing, total devotion, and spiritual self-learning. In the poem "Namamu," love is interpreted as existential longing expressed through the symbols of name, rain, time, and yearning. In "Kesaksian," love is represented as total devotion involving the whole human existence through bodily symbols and active diction. Meanwhile, "Cita-Cita Rindu" portrays love as an inner learning process symbolized by the figure of a teacher and the transformative function of longing. These findings indicate that love in Arrumy’s poetry extends beyond romantic relationships and encompasses emotional, existential, and spiritual dimensions. This study contributes to contemporary Indonesian literary studies by demonstrating the relevance of Ricoeur’s hermeneutics in uncovering deeper layers of meaning within poetic texts.